PEMBINAAN JURU PARKIR OLEH DINAS PERHUBUNGAN KOTA PEKANBARU - Sondang, Nidia; Sadad, Abdul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
Parking attendant guidance is an activity to encourage and motivate parking attendants in trying to develop and strengthen the potential in carrying out their responsibilities as a parking attendant and can also raise awareness of their potential. The purpose of this study was to determine and analyze parking attendant guidance by the Pekanbaru City Transportation Agency. This study uses the coaching theory of Santoso (2010) which uses 4 indicators, namely: the existence of guidance, provision of a forum, education and training, in the field. The research method used is a qualitative research method with data collection techniques: interviews, observation and documentation. The results of this study indicate that the parking attendant coaching by the Pekanbaru City Transportation Agency has been running but has not been optimal. This can be seen from the results of the research that there are several parts of the indicators in the coaching concept that have not been fulfilled, namely the provision of guidance, education and training and direct involvement in the field. The parts of the indicators that have not been fulfilled are caused by several factors, namely 1) human resource factors, lack of personnel to supervise parking attendants in carrying out their obligations. 2) the communication factor, the lack of communication that exists between the Department of Transportation, the UPTD of the Pekanbaru City Parking Area and the parking attendants, as one of them is the guidance provided by related parties is not carried out thoroughly and properly. 3) budget factor, there is no definite budget for parking attendant education and training activities. Keywords: Coaching, Parking Attendants.